Once the great lockdown is lifted: Post COVID-19 options for the economy - Jozef M. Ritzen (United Nations University (UNU), Maastricht Economic and Social Research Institute on Innovation and Technology (UNU-MERIT), 2020)
In 2021 lockdowns still will be necessary to keep COVID-19 in check world-wide. Vaccination might bring sufficient coverage by the end of 2021 for some countries. Priorities in the re-emergence of economies should be for sustainability, health, education, full employment and social cohesion to preserve long-term welfare. Pressures on Government budgets are going to rise in view of the unprecedented high public debt to GDP ratio world-wide. Increased taxation of wealth and of the top 10%-income-group is a superior strategy compared to retrenchment (budget cuts in health, education and social expenditures). International cooperation is top priority. This applies to health, but also to economic and monetary policy: it can lift economic growth in the G20 countries over the short and long run by at least one third. The resumption of trade should be guided by rewarding the achievement of social goals and realizing sustainability. In this way the level playing field is restored for those countries which want to contribute to a sustainable world and to cooperation. International taxation rules for profits should prevent tax havens to make this a negative sum game. This would give developing countries some of the necessary breathing space to re-emerge from the COVID-19 crisis.
Keywords: I00; J20; H63; H74; O38; O40; O43; O44; E62; E43; Q58; F18; F23; O52; R30; I25; F30; G15; H25; H87; 330; COVID-19; employment; economic development; environmental sustainability; social cohesion; education; health; monetary policy; long-term interest rates; conditionalities; taxation; stock market